Research on the Renovation Design Path for Enhancing the Efficiency of Mixed-Use Office and Retail Spaces - Liang, Qiyuan (European Journal of AI, Computing & Informatics, 2026)
Urbanization and the evolving demands of modern commercial environments have increasingly highlighted the necessity for sustainable urban renewal, particularly concerning existing building stock. This article focuses on how to systematically enhance the operational and spatial efficiency of mixed-use office and retail spaces during the process of existing building renovation. By conducting a comprehensive analysis from the perspective of architectural space design, this study addresses the inherent complexities of integrating diverse functional requirements within a single structure. After clarifying the core principles of spatial organization for multi-functional environments and establishing a renovation framework based on benefit orientation, specific analyses are conducted on critical issues. These include functional layout optimization, pedestrian flow organization, dynamic space usage, and the provision of human-centric facilities. To resolve these challenges, multiple targeted strategies are proposed, such as reshaping functional relationships, optimizing circulation route design, implementing flexible space conversions, and integrating advanced building facilities and smart technologies. Furthermore, a rigorous quantitative indicator system and detailed case comparisons are utilized to empirically evaluate changes in space efficiency, flow intensity, and overall energy consumption. The analytical results demonstrate that, under the premise of optimizing both the spatial structure and underlying business strategies, the proposed design path can effectively improve the utilization rate of composite spaces and enhance management orderliness. Ultimately, this research provides a robust theoretical foundation and practical reference for future sustainable renovation projects in high-density urban contexts.